Proximity‐dependent biotinylation reveals an interaction between ubiquitin‐specific peptidase 46 and centrosome‐related proteins - Kazuma Yoshioka; Reiko Nakagawa; Chi Lieu Kim Nguyen; Hayate Suzuki; Kiyohiro Ishigaki; Seiya Mizuno; Tsukasa Okiyoneda; Shizufumi Ebihara; Kazuya Murata (FEBS Open Bio)
Protein ubiquitination extensively modulates protein functions and controls various biological processes, such as protein degradation, signal transduction, transcription, and DNA repair. Ubiquitination is a reversible post‐translational modification, and deubiquitinating enzymes cleave ubiquitin from proteins. Ubiquitin‐specific peptidase 46 (USP46), a deubiquitinase, is highly expressed in the brain and regulates neural functions. Deleting lysine 92 (ΔK92) in USP46 reduces murine depression‐like behavior in the tail suspension test. However, the molecular basis for USP46's role in regulating neural function has not yet been fully understood. Here we employed a proximity‐dependent biotinylation approach to characterize the USP46 protein interaction partners. Using homology‐independent targeted integration (HITI), a genome editing technique, we established knockin cell lines that stably express USP46 wildtype‐ or ΔK92‐biotin ligase fusion protein. We identified 286 candidate interaction partners, including well‐known binding partners of USP46. Although there were no obvious differences in the interactome of USP46 between wildtype and ΔK92, a gene ontology analysis revealed that centrosome‐related proteins were significantly enriched in the proximal proteins of USP46. Several centrosome‐related proteins were bound to USP46 in Neuro2a cells, but their protein expression levels were not affected in the brains of USP46‐deficient mice. These results uncover a potential relationship between USP46 and centrosome regulation independently of protein stabilization.